2013
DOI: 10.4414/smw.2013.13732
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of dabigatran for stroke prevention in atrial fibrillation in Switzerland

Abstract: Dabigatran can be considered cost-effective in comparison with vitamin K antagonists in the Swiss context. The higher drug cost of dabigatran is compensated by savings in INR monitoring, lower cost of clinical events and QALY-gains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 34 publications
1
22
0
1
Order By: Relevance
“…Twelve studies with single technology assessments of dabigatran compared with VKAs covering eight countries were identified in PubMed. Among these, six studies [33][34][35][36][37][38] adapted the model from Sorensen et al [10] and assessed the cost-effectiveness of dabigatran 150 or 110 mg bid according to age. The other studies assessed different treatment courses, including assessing 150 and 110 mg bid separately, comparing dabigatran to warfarin, aspirin and clopidogrel, or focusing on sub-groups based on age or risk level measured by CHADS 2 score [39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Twelve studies with single technology assessments of dabigatran compared with VKAs covering eight countries were identified in PubMed. Among these, six studies [33][34][35][36][37][38] adapted the model from Sorensen et al [10] and assessed the cost-effectiveness of dabigatran 150 or 110 mg bid according to age. The other studies assessed different treatment courses, including assessing 150 and 110 mg bid separately, comparing dabigatran to warfarin, aspirin and clopidogrel, or focusing on sub-groups based on age or risk level measured by CHADS 2 score [39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Not only would large quantities of therapy changes challenge patients and clinicians, but the mass of new NOAC prescription would also have relevant economic influence on the country's obligatory health insurance system covering anticoagulant treatment. It has been shown that NOACs can be cost-effective in specific settings despite higher pharmaceutical costs, because overall costs for anticoagulation related outpatient visits and hospitalizations were reduced compared to warfarin treatment [80][81][82][83][84]. However, just like clinical outcomes, also cost-efficiency estimations have been demonstrated to depend on TTR levels achieved in the VKA group [85,86].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, dabigatran was superior to warfarin in terms of quality-adjusted life years and the incremental cost-effectiveness ratio [31]. Similarly, in another study, the higher cost of dabigatran was negated by savings in INR monitoring and a lower cost of clinical events than with warfarin [32]. …”
Section: Introductionmentioning
confidence: 98%